2002
DOI: 10.1172/jci200215334
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 2 and 9 work in concert to produce aortic aneurysms

Abstract: Matrix metalloproteinases (MMPs) 9 and 2 are increased in human abdominal aortic aneurysm (AAA) tissue, but their precise role and potential interaction remain unclear. Experimental induction of aortic aneurysms in mice genetically deficient in these peptidases could provide new insight into AAA pathogenesis. Mice deficient in the expression of MMP-9 (MMP-9KO) or MMP-2 (MMP-2KO) and their corresponding wild-type background mice (WT) underwent AAA induction by abluminal application of calcium chloride (CaCl 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
3

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 31 publications
4
65
0
3
Order By: Relevance
“…This result confirms previous reports where MMP-2 and MMP-9 may be crucial at the early stages of AAA development in this model [17], and that MCT-1-mediated inhibition of MMP-2 and MMP-9 expression may contribute to the reduction in AAA formation and severity. This is consistent with a previous study that demonstrated that both MMP-2 and MMP-9 knockout mice are resistant to aneurysm development [18]. …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This result confirms previous reports where MMP-2 and MMP-9 may be crucial at the early stages of AAA development in this model [17], and that MCT-1-mediated inhibition of MMP-2 and MMP-9 expression may contribute to the reduction in AAA formation and severity. This is consistent with a previous study that demonstrated that both MMP-2 and MMP-9 knockout mice are resistant to aneurysm development [18]. …”
Section: Discussionsupporting
confidence: 94%
“…2a, b, fig. 4) protein, previously identified as critical to AAA development [18], was demonstrated with MCT-1 treatment and suggests a mechanistic explanation for reduced AAA incidence and severity identified in MCT-1-treated animals in vivo. In addition, previously described HDACi-mediated inhibition of pro-inflammatory genes [37, 38], implicated in AAA pathogenesis, may also contribute to the mechanism of action of MCT-1 in our study.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Accelerated matrix breakdown caused by increased activity of MMPs and/or quantitative imbalance between MMP and their inhibitors can result in vascular diseases [1,2,3]. Indeed, increased circulating levels and in situ overexpression of MMP-2, MMP-9 and elastase have been detected in adult humans with aortic and intracranial aneurysms, suggesting an important role for some proteases in arterial wall destruction and resultant aneurysm formation [2,3,4,5,6,7,8,9,10]. These findings raise the possibility that proteases might also be involved in the pathophysiology of spontaneous cervical artery dissection (SCAD), a vascular disease supposed to be related to a yet unidentified ECM defect or fragility [11,12,13,14] and associated with intracranial aneurysms [15, 16].…”
Section: Introductionmentioning
confidence: 99%